Geologi dan Mineralisasi Uranium di Sektor Sarana Kalan, Kalimantan Barat Berdasarkan Data Pemboran - Sartapa, Sartapa; Sukadana, I Gde (EKSPLORIUM, 2011)
Favourable zone of uranium mineralization in Sarana Sector with NE-SW direction are contained in metapelite rock and some in muscovite quartzite. Mineralization of uranium is occurred fill in the fields of parallel fractures with schistosity by ENE-WSW direction, and moderate to strong inclination to the north. Three points drilling with the depth of 126.6, 174.50, and 150.90 meter has been conducted. This study is aimed to obtain the knowledge of geology, and geometry of sub-surface uranium mineralization. Geologically, research area are consists of metapelite, muscovite quartzite and biotite quartzite with millimetric - centimetric thicknesses. Uranium mineralization are in forms of veins or tabular as uraninite and pitchblende associated with pyrite, chalcopyrite, pyrrhotite, ilmenite and molydenite. Uranium Mineralization on the surface could be correlated with sub-surface from bore-hole data, with the result that zone of uranium mineralization in lenses or tabular form with sub-vertical dip may be identified.